2011
DOI: 10.1177/1363459311403944
|View full text |Cite
|
Sign up to set email alerts
|

Smoking and workers’ autonomy: A qualitative study on smoking practices in manual work

Abstract: A massive amount of research has brought out the association of daily smoking with social class. Smoking remains very common in the most disadvantaged groups, but it has also maintained its popularity among manual workers. The starting point of the article is that what needs to be taken into account in explaining the social differentiation of smoking is the social context in which smoking takes place. The study is based on interviews of daily smokers, ex-smokers and occasional smokers from different occupation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…The marginally significant finding that lower-SES smokers expected more negative support than higher-SES smokers corresponds with work by Sorensen et al (2002), who showed that general support was less available to lower-SES smokers (see also Katainen, 2011). Importantly, negative support can be harmful (Lawhon et al, 2009;Roski et al, 1996) and might be interpreted as negative reactions from the social environment (e.g., questioning ability to quit).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The marginally significant finding that lower-SES smokers expected more negative support than higher-SES smokers corresponds with work by Sorensen et al (2002), who showed that general support was less available to lower-SES smokers (see also Katainen, 2011). Importantly, negative support can be harmful (Lawhon et al, 2009;Roski et al, 1996) and might be interpreted as negative reactions from the social environment (e.g., questioning ability to quit).…”
Section: Discussionmentioning
confidence: 96%
“…Higher-SES smokers experience more social pressure to quit than lower-SES smokers, and are more likely to become socially marginalized with continued smoking (Christakis and Fowler, 2008;Royce et al, 1997;Sorensen et al, 2002). Conversely, a qualitative study among blue-collar workers showed that quitting smoking was perceived as 'leaving the gang', and that group members attempted evoke relapse to keep the quitter within the group (Katainen, 2011). This can be explained by social identity theory, which states that people derive an important part of their identity from their membership in groupsdsocial identity (Tajfel and Turner, 1979).…”
Section: Introductionmentioning
confidence: 99%
“…Most studies comparing smoking motives between population subgroups are relatively small (Klitzke et al 1990; Livson and Leino 1988;Shiffman and Prange 1988;Souza et al 2010;Tate et al 1994;West and Lennox 1992), or they are limited to specific patient groups (Peretti-Watel et al 2009). They might also be qualitative (Katainen 2010(Katainen , 2012, and we found only two studies on smoking motives conducted among the general population (Fidler and West 2009;Yong and Borland 2008), and even then, only a limited number of motives were covered.…”
Section: Introductionmentioning
confidence: 95%
“…The motives for smoking may differ according to age (Klitzke et al 1990), with older smokers more often than younger ones reporting enjoyment as their motive (Fidler and West 2009). People belonging to higher social classes perceive smoking as fulfilling some positive function such as stimulation and better mental performance, while those in the lower classes lack such explanations and see smoking as a routine action or as a consequence of addiction (Katainen 2012). Most studies comparing smoking motives between population subgroups are relatively small (Klitzke et al 1990; Livson and Leino 1988;Shiffman and Prange 1988;Souza et al 2010;Tate et al 1994;West and Lennox 1992), or they are limited to specific patient groups (Peretti-Watel et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Graham 1993, 1994; Greaves 1996; Gillies and Willig 1997; McKie et al. 2003; Katainen 2006, 2012; Denscombe 2001, 2010; Haines et al. 2009; McCullough 2011).…”
Section: Beyond Standard Tobacco Control Perspectivesmentioning
confidence: 99%